2013
DOI: 10.1021/nl303576q
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Controlled Nanoparticle Synthesis inside Nanopores

Abstract: From their realization just over a decade ago, nanopores in silicon nitride membranes have allowed numerous transport-based single-molecule measurements. Here we report the use of these nanopores as subzeptoliter mixing volumes for the controlled synthesis of metal nanoparticles. Particle synthesis is controlled and monitored through an electric field applied across the nanopore membrane, which is positioned so as to separate electrolyte solutions of a metal precursor and a reducing agent. When the electric fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 31 publications
1
36
0
1
Order By: Relevance
“…[8][9][10][11] While faceted nanopores can be potentially employed in rapid electrical detection and analysis of biomacromolecule with various shapes, the relevant investigation has been rarely reported. 14 In addition, Venta et al recently showed the synthesis of electrically controlled gold nanoparticles inside nanopores, 15 indicating that an individual nanopore can serve as a "nano-mold" regarding the synthesis of nanomaterials. Owing to the high-aspect-ratio, nanoparticles with different shapes and facets could exhibit drastically different electrical, 16,17 optical, 18,19 and catalytic 20,21 properties.…”
Section: Fabrication Of Faceted Nanopores In Magnesiummentioning
confidence: 99%
“…[8][9][10][11] While faceted nanopores can be potentially employed in rapid electrical detection and analysis of biomacromolecule with various shapes, the relevant investigation has been rarely reported. 14 In addition, Venta et al recently showed the synthesis of electrically controlled gold nanoparticles inside nanopores, 15 indicating that an individual nanopore can serve as a "nano-mold" regarding the synthesis of nanomaterials. Owing to the high-aspect-ratio, nanoparticles with different shapes and facets could exhibit drastically different electrical, 16,17 optical, 18,19 and catalytic 20,21 properties.…”
Section: Fabrication Of Faceted Nanopores In Magnesiummentioning
confidence: 99%
“…Highly sensitive electronics allows detection of very small changes in the conduction current, facilitating high-resolution size discrimination. The simplicity of the concept linked with the versatility of the method has led to the use of solid-state pores for a wide range of applications involving micro-and nanosized particles, [5][6][7][8][9] polymer chains [10] and proteins. [11][12][13][14] The capability of the technology to facilitate rapid and direct evaluation of individual DNA bases has made it particularly attractive for next-generation DNA sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…At present, an intensive search has been carried out for low-cost effective methods of synthesizing such nanocomposites. In particular, the authors of [9][10][11][12][13] proposed a number of simple effective solid-phase chemical synthesis techniques with the features similar to those of the method used in the present study.…”
Section: Introductionmentioning
confidence: 99%